Implementation of Collaborative Learning Model Teaching and Learning Life Skills based for Improving the Competence of Students in Facing the Industrial Revolution 4.0 and the Society 5.0 Era - Cucu Sutianah; Mumu Mumu; Tetty Fatimah Tsuroya (Budapest International Research and Critics University, 2022)
The implementation of learning should stimulate students to be more active in improving social skills, emotional skills, spiritual skills, scientific skills, mental skills, kinesthetic skills, and entrepreneurial skills, which in turn can improve students' competence and entrepreneurial character, in accordance with the vision and mission Education units. These skills are also skills needed in the world of work and industry, because industry professionals always work in groups and synergize to complete a particular project or job. Thus, the hard skills and soft skills of vocational and high school students as prospective workers and entrepreneurs should be able to develop creativity and innovation that will shape competence, entrepreneurial character, through positive, integrated, combined, mutual cooperation and collaboration interactions, implementing human literacy among people. Fellow human beings, cooperate, work in groups, synergize, and collaborate to complete a job. Life skills in the Industrial Revolution 4.0 and the era of society 5.0, as well as the new normal life, are the ability and courage to face life's problems, then proactively and reactively, seek and find solutions to overcome them. Life skills are skills or abilities to be able to adapt and behave positively, which allows a person to be able to deal with various demands and challenges in real life more effectively. The implementation of life skills-based collaborative learning can be used as a forum to improve students' competence and entrepreneurial character.